Solvometallurgical Extraction of Refractory Gold using Deep Eutectic Solvents - Reyes, Joanna; Oliva, Luke Bernard III; Resuello, John Rossmon; Maniaul, Joy Mirasol; Ramirez, Paolo Aiman; Tungpalan, Djoan Kate (Philippine Engineering Journal, 2025)
The extraction of gold from refractory ores presents a significant challenge in the mining industry. This study investigates a novel approach of using deep eutectic solvents (DES) mixtures in extracting gold from refractory ores. Comparative leaching experiments were conducted on a refractory gold ore (P80 37 μm) at 30°C, employing choline chloride as the HBA and four HBDs: urea, malonic acid, ethylene glycol, and oxalic acid. The highest gold concentration (2.95 ppm) and recovery (48.9%) were achieved with the choline chloride-oxalic acid DES, with a clear trend of increasing gold extraction corresponding to increasing HBD acidity. The influence of temperature (30–60°C) and solids-to-lixiviant ratio (1:15 to 1:25) on gold extraction using the choline chloride-oxalic acid DES was then investigated. Results demonstrated that lower temperatures and higher lixiviant ratios significantly enhance gold extraction. These findings highlight the significant potential of DES to improve the efficiency and sustainability of refractory gold processing. Keywords: deep eutectic solvents, refractory gold, choline chloride, gold extraction